TM6SF2 rs58542926 is related to hepatic steatosis, fibrosis and serum lipids both in adults and children: A meta-analysis - Li, Xue-Ying; Liu, Zheng; Li, Li; Wang, Hai-Jun; Wang, Hui (Frontiers in Endocrinology, 2022)
Background and Aims: Findings about the associations between transmembrane 6 superfamily member 2 (TM6SF2) rs58542926 and nonalcoholic fatty liver disease have not been consistently replicated, particularly in steatosis and fibrosis. The present study aimed to investigate the associations between the rs58542926T allele and the spectrum of NAFLD and its related metabolic phenotypes. Methods: Systematic literature research was performed to analyse the associations between rs58542926 and the spectrum of NAFLD and its related metabolic phenotypes. A random effects meta-analysis with a dominant genetic model was applied. Results: Data from 123,800 individuals across 44 studies were included in the current meta-analysis.rs58542926 T allele was associated with an increased risk of NAFLD in both adults (OR=1.62; 95% CI: 1.40, 1.86) and children (OR=2.87; 95% CI: 1.85, 4.46). Children had a stronger association with NAFLD (P=0.01). rs58542926 T allele was also positively associated with steatosis progression (mean difference=0.22; 95% CI: 0.05, 0.39) and fibrosis stage (OR=1.50; 95% CI: 1.20, 1.88) in adults. The TM6SF2 rs58542926 T allele was positively associated with ALT in both adults and children (both P<0.01) and only with higher AST in adults (P<0.01). The rs58542926 T allele was negatively associated with serum total cholesterol (TC), low-density lipoprotein (LDL), and triglycerides (TGs) in both adults and children (all P<0.01).The serum level of TG was much lower in adults than in children (P<0.01). Conclusion: TM6SF2 rs58542926 is involved in the entire spectrum of NAFLD and its related metabolic phenotype, and differences in serum lipid levels were observed between adults and children.